Der Essay als Form der Darstellung sozialwissenschaftlicher Erkenntnisse - Bude, Heinz (online, 1989)
Abstract: Refering to the long tradition of essayistic writing in sociology, beginning with Georg Simmel over Albert Salomon, Alfred Schütz, Kurt H. Wolff and Theodor W. Adorno up to Erving Goffman, the essay is conceived as a classical form of presenting sociologcal ideas. The formal principles of this sociological art form are reconstructed: the steps of the essayistic sequence, the rhetoric figures used, the type of phrases essays are typically using. Discussing the theoretical implications of these formal principles it is stated that the essay is not only a form of presenting sociological ideas but also a form of finding sociological ideas. Essayistic theorizing turns out to be a specific type of sociological thinking. Taking the example of Karl Weik's Social Psychology of Organizing it is shown how the essayistic
urn:nbn:de:0168-ssoar-40867
Keywords: Adorno; Theodor W.; Musil; Robert; Bude; Heinz; Bütow; Hans; (thesoz)Transfer; (thesoz)Wissenschaft; (thesoz)Essay; (thesoz)Erkenntnis; (thesoz)Rhetorik; (thesoz)Sozialwissenschaft; (thesoz)Soziologie; (thesoz)Formalisierung; Essayist; Erkenntnis